(untitled) (International Journal of Engineering and Computer Science, 2017)
The rapidly advancing mobile communication technology and the decrease in costs make it possible to incorporate mobile technology into Smart Home systems. We propose a mobile and internet based Smart Home system that consists of a mobile phone with android capabilities, an internet based application, and a home server. The home appliances are controlled by the Arduino which receives commands from the server computer, which operates according to the commands received from the mobile application via the wireless network or the internet. In our proposed system the home server is built upon a Wi-Fi technology which receives commands from the client and the command is processed via Arduino, which allows a user to control and monitor any parameters related to the home by using any Andriod capable smart phone or via the internet. This paper presents an innovative low cost design and implementation of automated control based on weather conditions, appliance control, and, home security together with the design of android application to enable the smart phone to send commands and receive alerts through the server based system.